Kawasaki Disease Complicated With Macrophage Activation Syndrome: Case Reports and Literature Review - Jin, Ping; Luo, Yong; Liu, Xi; Xu, Jinji; Liu, Chunyi (Frontiers in Pediatrics, 2019)
Macrophage activation syndrome (MAS) is a rare and severe complication of Kawasaki disease (KD). The clinical feature, early diagnosis and treatment options, and prognosis need to be further determined in patients with KD complicated with MAS. In this report, we retrospectively analyzed three KD patients complicated with MAS who were treated in pediatric intensive care units (PICU) and reviewed the relevant literatures. We find that being male, being age over 2 years old, incomplete KD, intravenous immunoglobulin (IVIG) non-responder, or persistent fever greater than 10 days are all highly associated with occurrence of MAS. Additional work-ups should be performed promptly in patient with above predisposing factors to rule out complication of MAS. Patients with KD complicated with MAS are at a higher risk of having coronary artery involvement or aneurysm formation, which can be reversed with timely treatment. Early identification and prompt treatment are key points for improving the prognosis of KD patients complicated with MAS.